Magnitude of thyroid disorders: Global epidemic and Bangladesh perspective - Siddiqui, Md Nazrul Islam (Journal of Association of Clinical Endocrinologist and Diabetologist of Bangladesh, 2025)
Abstract not available J Assoc Clin Endocrinol Diabetol Bangladesh, July 2023;2(2): 35-38